2019
DOI: 10.1016/j.omtn.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Long Noncoding RNA and mRNA Profiles in Sepsis-Induced Myocardial Depression

Abstract: Septic shock with heart dysfunction is very common in intensive care units. However, whether long noncoding RNA (lncRNA) and mRNA profiles differ between patients with and without myocardial depression is unknown. We generated rat models of hypodynamic septic shock induced by lipopolysaccharide. A total of 12 rat models was constructed and heart tissue from each was collected. Whole genomic RNA sequencing was performed on left ventricular tissue; 6,508 novel lncRNAs and 432 annotated lncRNAs were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(89 citation statements)
references
References 27 publications
3
85
1
Order By: Relevance
“…As mentioned previously [ 2 , 12 ], our group has found that there is a positive relationship between the MAP and heart function. In this study, septic shock occurred at approximately 2 hours after LPS injection, and the MAP of the control groups remained unchanged ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…As mentioned previously [ 2 , 12 ], our group has found that there is a positive relationship between the MAP and heart function. In this study, septic shock occurred at approximately 2 hours after LPS injection, and the MAP of the control groups remained unchanged ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 72%
“…Based on the sequencing results described previously [ 9 , 12 ], we selected certain microRNAs for further analysis. The target genes of the differently expressed miRNAs were identified using the miRanda, PITA, and RNAhybrid databases [ 13 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several long non-coding RNAs (lncRNAs) (data not shown), were also significantly regulated in the septic heart samples. Such lncRNAs are in a rat model, suggested play an interaction and regulation role in the pathogenesis of sepsis-induced myocardial depression (Zhang T. N. et al, 2019).…”
Section: Transcriptional Profiles In Heart Tissue Samplesmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a class of RNA that are longer than 200 nucleotides, and with no protein-coding potential [8]. They modulate gene expression at different levels, including chromosome reconstruction, transcription, and post-transcription [9]. LncRNAs play various critical biological functions such as acting as signaling, decoy, guide, and scaffold molecules [10].…”
Section: Ivyspringmentioning
confidence: 99%